Fish eDNA detection and its technical optimization: A case study of Acanthopagrus latus. (April 2022) - Sun, Meijing; Guo, Yu; Zhao, Naiqian; Zhang, Shuo; Pei, Kun; Qin, Chuanxin
Abstract: The development of a standardized eDNA detection process is the primary step in improving the accuracy and efficiency of eDNA detection. In this study, primers and probes with high specificity were selected to identify the COI gene of Acanthopagrus latus . Through experiments on the influence of different water quantities, methods of water sample preservation and water bathing times on the result of eDNA detection, the accuracy of this method for extracted water samples was improved. Specifically, a water bathing time of 6 h provided an optimal eDNA concentration from the water sample. After 6 h, the concentration began to decrease, so 6 h was determined to be the best water bathing time for A. latus. Five water extraction volumes (250 mL, 500 mL, 1 L, 2 L, and 3 L) were tested, and there was a positive correlation between water extraction volume and the DNA concentration in the water sample. Different water sample preservation methods were also compared, and it was found that at ≤7 d, the concentration obtained with the cryopreservation method for different water extraction volumes was higher than that obtained with the ethanol preservation method. In this study, we established and optimized a technical procedure for eDNA-based detection of A. latus in aquatic environments. We hope to apply this method in field investigations and provide a reference for the study of eDNA in other fishes. Highlights: Using collected Acanthopagrus latus, we applied molecular technology to design fluorescent primers and TaqMan probes to identify the target species ( A. latus ). By optimizing the methods and parameters of water sampling for DNA extraction and preservation, the process for applying eDNA technology in A. latus was preliminarily established, optimizing the water volume needed for DNA extraction. This finding is of great significance for eDNA detection in relation to resource conservation in A. latus and provides a reference for developing eDNA detection processes for other species.